Efeitos causados pelo veneno da Hoíhrops moojeni e de suas frações miotoxina I e II em rim isolado de rato - Barbosa, Paulo Sérgio Ferreira (2002)
Acute failure renal is one the most common systemic complications after snakebite, however, its pathogenesis remains obscure. In this study we evaluated the renal effects of Bothrops moojeni venom and its miotoxins (Bmtx-I and BmtxII) in rat isolated perfused kidneys. The miotoxins were purified by ion-exchange chromatografy and reverse phase HPLC. The crude venom (10 pg /mL) and myotoxins (5 pg/mL) were added to the perfusion system 30 min after the start of perfusion. The renal effects were compared with a control group, perfused with modified Krebs-Henseleit solution alone. B. moojeni venom decreased the perfusion pressure (PP), renal vascular resistance (RVR), and the percent sodium, potassium and chloride tubular transport (%TNa+, %TK+ %TCf). In contrast, the venom increased the urinary flow (UF), glomerular filtration rate (GFR), and the sodium, potassium and chloride excretion (ENa+, EK+, ECF). The renal effects of myotoxin I were very similar to those of the venom, but there was an increase rather than a decrease in the PP and RVR. Myotoxin II had no effect on renal physiology, except for a transient decrease in %TK+. In conclusion, Bothrops moojeni venom caused intense alterations in renal physiology, including a drop in vascular resistance associated with diuresis, natriuresis and kaliuresis. Bmtx-I had an opposite effect to that of crude venom in PP and RVR. Bradykinin potentiating peptides in the venom could contribute to the decrease in vascular resistance. BmTx-I may have exerted its renal effects by indirectly increasing the calcium influx after damage to the cell membrane.